Equilibrium Investment Strategies and Output Price Behavior: A Real-Options Approach - Aguerrevere, Felipe L. (Review of Financial Studies, 2003)
The effects of competitive interactions on investment decisions and on the dynamics of the price of a nonstorable commodity are studied in a model of incremental investment with time to build and operating flexibility. I find that an increase in uncertainty may encourage firms to increase their capacity. Furthermore, I show that it may be optimal to invest in additional capacity during periods in which part of the operational capacity is not being utilized. The impact of competition on the properties of the endogenous output price is dramatic. For example, I find that price volatility may be increasing in the number of competitors in the industry. Copyright 2003, Oxford University Press.